Sistem Perpipaan pada Green House di Panti Asuhan dan Pondok Lansia Al – Maa’uun Sapuran, Wonosobo, Jawa Tengah - Sugiyanto, Sugiyanto; Krisnaputra, Radhian; Winarto, Felik Eko Wismo; Ismail, andhi Akhmad; Bahari, Galuh; Nur Esa, Suhada; Nur Hidayatulloh, Fikhih (Politeknik Negeri Jember, 2024)
Panti Asuhan dan Pondok Lansia